UKURAN PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP TERJADINYA KONDISI FINANCIAL DISTRESS - Anne Selvytania; Ellen Rusliati (Jurnal Riset Bisnis dan Manajemen, 2019)
This study aims to determine how the influence of firm size and good corporate governance on the occurrence of financial distress in various industrial sector companies listed on the Indonesia Stock Exchange during 2012-2017. The research method used is descriptive and verifiative. The sample used were 5 sector companies which were done by purposive sampling. Data analysis method used was panel data regression analysis using Eviews 9. The results showed that simultaneously the size of the company and good corporate governance have effect on the occurrence of financial distress conditions about 69.2%. Partially the size of the company has an effect of 39.7%, institutional ownership has an effect 22.4% on the occurrence of financial distress, while managerial ownership has an effect of 7.1% but not significant.